Surgical acute abdomen in elderly patients. - Itengré Ouédraogo; Julio Pablo Miñoso Andina; Angel Delfín Rodríguez Sarria; Lidia Torres Ajá (Medisur)
Fundaments : The surgical acute abdomen usually is the most frequent cause of abdominal surgery of urgency in t he old one, with the high mortality in spite of the modern surgical technologies. Objective: To evaluate the surgery of the surgical acute abdomen in the old one. Method: Appears a prospectivo descriptive study that includes 102 patients of 60 years or more who underwent surgery at the ¨Dr Gustavo Aldereguía Lima¨ University Hospital of Cienfuegos with this diagnostic. The primary data were obtained from clinical cards of the patients and the daily clinical observation until the debit. Results: The patients presented an average age of 74 years, being the most frequent causes of the syndrome intestinal obstruction (32,4%), the biliary tract affections (22,5%), and acute appendicitis (21,6%). The most frequent symptom was abdominal pain (96,08%), and we noticed tachycardia in 80,4%. Postoperating complications in 47,06% of the patients appeared and was observed a mortality of 26,5% with statistically significant relation with the age, ASA classification, surgical risk, time of evolution and the surgical time. The peritonitis heads the direct causes of death.